Heat Shock Lipolysis: Radiofrequency Combined with Cryolipolysis for the Reduction of Localized Subcutaneous Fat - S. Abboud; J. P. Hachem (Hindawi Limited, 2020)
Introduction. Noninvasive procedures such as cryolipolysis, noncontact selective radiofrequency (RF), and laser selective fat heating have been shown to be safe and effective for the reduction of localized subcutaneous fat. Material and Methods. In this retrospective study, we describe the safety and efficacy of combining RF with cryolipolysis for localized unwanted fat after one single session. 69 patients, 61 females, and 8 males for a total of 75 treatments were included in this study. All patients underwent RF prior to and following cryolipolysis. Pictures (n = 24), taken before and after treatment, were used to clinically assess the physician Global Aesthetic Improvement Scale (PhGAIS). In parallel, patients were asked to subjectively evaluate the efficacy of the treatment using the same scale (PaGIAS). Results. PhGIAS showed an improvement in 18 patients (73.46%), 5 (22.44%) were unchanged, and 1 (4.08%) worsened their appearance after treatment. The mean PaGIAS scored as "good improvement." Conclusion. In conclusion, combining RF with cryolipolysis in one single session is safe and effective.